DIAGNOSIS OF THE LEVEL FORMATION OF PROFESSIONAL PSYCHOLOGICAL COMPETENCE OF FUTURE TEACHERS - Chernuha, Nadiya; Savrasova-V’un, Tat’yana (Continuing Professional Education: Theory and Practice, 2023)
The article describes the essence of the structure of professional and psychological competence of future teachers. The criteria, indicators, levels of formation represented by the phenomenon. Streamlined system diagnostic tools to determine the level of development of professional psychological competence of future teachers. Vocational-psychological competence of the future teachers - is an integrative quality of a person of the future teachers, which contains a set of psychological knowledge, skills, values, motivations, emotional, volitional processes aimed at effective implementation of professional work and self-improvement. The structure of vocational and psychological competence of the future teachers by us include the following components: motivational-value, emotional and evaluative, actively-willed, professional and personal, cognitive orientation. Motivational-value criterion serves as a set of conscious motives that determine the choice of action to improve the psychological skills. Emotional and evaluative criteria is characterized as a complex relationship to the use of psychological knowledge and skills in their professional activities. Operations-willed criterion represented as a set of skills, skills to apply psychological knowledge in their professional activities. Professional and personal criterion is defined as a set of professional, personal qualities, characteristics, abilities, contributing to effective professional activity. Cognitive orientation criterion is characterized as a set of psychological knowledge and methods of application of this knowledge in professional activity